Change of direction speed and deficit over single and multiple changes of direction: Influence of biological age in youth basketball players - Gonzalo-Skok, O.; Bishop, C. (Journal of Sports Sciences, 2023)
The study analysed the difference in change of direction (COD) deficit among young male basketball players of different age groups and biological ages and analysed the relationships in COD performance (time and deficit) across single and multiple CODs depending on their biological age. Fifty-four highly-trained male players (U-13 and U-17) were tested on sprinting (25-m) and COD ability over single and multiple CODs through total times and the percentage-based COD deficit (CODD). Results showed that older age groups performed significantly (ES = 0.43-2.32, p < 0.05) better in linear and COD times, especially those players with post-peak height velocity (PHV) (ES = 0.89-1.90). Controlling for age at PHV, no significant differences were found in any group or inter-limb asymmetries. Moderate relationships were found between CODD in the pool data (r = 0.36 to 0.50). All CODD and time relationships in any test (i.e., 180º COD and V-cut) were considerably lower (r= -0.27 to 0.32) across individual biological groups. The study highlights the impact of maturation on COD performance, whereas CODD seems to be not affected. Interestingly, the CODD is independent, highlighting this measurement`s specific nature. Practitioners should use common distances, angles, and the number of CODs linked to biological status to create a COD profile.